Contingency contracting with disadvantaged youths: Improving classroom performance - Kelley, Mary Lou (1982)
This study evaluated the effects of a student-teacher contracting procedure on adolescent students' academic productivity. Participants were 13 youths enrolled in a vocational training program for disadvantaged youth and their classroom teacher. During the baseline conditions students were paid contingent on attendance alone, the system operating in the program prior to this research. During contracting conditions students were paid contingent on contract fulfillment of academic productivity goals set by mutual agreement between the student and teacher. Contracting and contingent pay procedures were developed with, and implemented by, the classroom teacher. A reversal experimental design showed that student's productivity more than doubled during contracting conditions as compared with their productivity during baseline.